Analysis of Factors Influencing Perceptions and Attitudes Towards Investment Decisions in Esg-Based Companies By Investment Analysts (Case Study on PT. Astra International TBK) - Shara Novalina (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the factors affecting investment analysts' perceptions and attitudes towards investment decisions in ESG (Environmental, Social, and Governance) based companies at PT. Astra International Tbk. With growing global emphasis on sustainability, understanding the determinants of ESG investment decisions has become critical for both practitioners and scholars. This study employs a qualitative approach with in-depth interviews involving investment analysts at PT. Astra International Tbk. Data were analyzed using NVivo 14 software through systematic coding and thematic analysis to identify patterns and relationships among variables. Results reveal that knowledge is the most influential factor in shaping perceptions and attitudes towards ESG-based investment decisions. Other significant factors include availability bias, social media influence, overconfidence, anchoring bias, herding behavior, representative bias, interest rates, loss aversion, and locus of control, while age demonstrates minimal influence. These findings provide practical implications for investment firms seeking to enhance ESG integration: companies should prioritize comprehensive ESG training programs, develop strategies to mitigate cognitive biases, and leverage digital platforms for effective ESG communication. This research contributes to behavioral finance theory in sustainable investing contexts and offers actionable guidance for developing robust ESG investment frameworks in emerging markets.